Student Difficulties in Solving High Order Thinking Skills (HOTS) Problem on Geometry Problems Viewed from the Cognitive Styles - Muslim Muslim; M. Ikhsan; Taufik Fuadi Abidin (Proceedings of AICS - Social Sciences, 2018)
The results of Indonesian students' mathematics learning scores from UN, PISA, TIMSS and INAP show unsatisfactory results, students are still weak in cognitive skills. Math learning aims to equip students with logical, analytical, systematic, critical, and creative thinking skills, as well as cooperative skills called higher order thinking skill (HOTS). The 2013 curriculum requires students to be familiar with HOTS issues. HOTS has a relationship and influences students' cognitive style. The purpose of the study to determine the difficulties of students in solving the problem of HOTS on geometric problems regarding cognitive style. Research using the qualitative approach, research subject consist of field dependent student (FD) and field independent (FI). Research instruments are HOTS test, interview, and GEFT test. Data analysis was done based on Miles and Huberman's stages: data collection, data reduction, data presentation, and conclusion. The results showed that: 1) FD students tend to experience difficulties in the transformation and coding stages, 2) FI students tend to experience difficulties in the process skill and coding stage.